If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -18 = 3x + 24 Reorder the terms: -18 + 2x = 3x + 24 Reorder the terms: -18 + 2x = 24 + 3x Solving -18 + 2x = 24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -18 + 2x + -3x = 24 + 3x + -3x Combine like terms: 2x + -3x = -1x -18 + -1x = 24 + 3x + -3x Combine like terms: 3x + -3x = 0 -18 + -1x = 24 + 0 -18 + -1x = 24 Add '18' to each side of the equation. -18 + 18 + -1x = 24 + 18 Combine like terms: -18 + 18 = 0 0 + -1x = 24 + 18 -1x = 24 + 18 Combine like terms: 24 + 18 = 42 -1x = 42 Divide each side by '-1'. x = -42 Simplifying x = -42
| 9x-9=5x+2 | | 6x+91=10x-13 | | 11+(-17)=-6 | | 12x-10=-6+8 | | 32-4x=5x+21 | | k=ab-5b-3a | | 10=-2/3m | | 2(t-4)+6t=4(2t+5)-10 | | 11m+3n-5m+9n= | | (a-8)/12=(2a+5)/3 | | 16x^2-8y^2-48x+40y-15=0 | | 7(x+4)=4x+1 | | 3(x-20)=12 | | 8-9x=103-44x | | 12-7x=112-35x | | Y=(2x+6)(0.5x+4) | | 3(x-20)=21 | | -(9/8)+(1/8)=-3/4 | | -16=6x | | x^3+10x^2+13x=0 | | 2x*2+10=210 | | 151-3x=6x-16 | | -5x*2=-500 | | 8-6x-2=40+4x-14 | | x*2+8=28 | | 30b= | | 4x+25-2x=6 | | 3x^2-27/x^2=0 | | x*2=76 | | 3x^2-27x^2=0 | | x*2-2=17 | | -12+x=54 |